Esta primavera fugitiva de Alberto Conejero (2021). El príncipe constante de Calderón de la Barca como el arte de vivir, sobrevivir y revivir - Baczyńska, Beata (L’art de vivre, de survivre, de revivre. Approches littéraires. Le 50e anniversaire des études romanes à l’Université de Łódź, 2022)
The article studies a theatrical project staged at Teatro de la Comedia in Madridby Alberto Conejero, with Susi Sánchez y José Troncoso, based on El príncipe constanteby Calderón: Esta primavera fugitiva (Varaciones sobre «El príncipe constante» de Calderón dela Barca). The performance was commissioned by Compañía Nacional de Teatro Clásicoand staged on 17th of March 2021. The playwright converged several voices in his personalrecast to manifest the strength and universality of El príncipe constante. The mise-enabymeeffect is stressed by the presence of Alberto in his play, as well as the mention ofJerzy Grotowski, Ryszard Cieślak and Juliusz Słowacki, the author of the Polish versionof The Constant Prince. Different testimonies confirm the fundamental function of theateras ars vitae.